2009
DOI: 10.1007/s10637-009-9224-x
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a model that predicts early death among cancer patients participating in phase I clinical trials investigating cytotoxics

Abstract: We do not recommend the enrolment of patients with albumin level below 38g/l and lymphocytes count below 700/mm(3), in phase 1 trial investigating cytotoxics. Our model is helpful to discriminate "patients with reasonable life expectancy" as defined in most phase 1 protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 35 publications
0
22
1
Order By: Relevance
“…could modify clinical practice and thereby permit to use lymphopenia for decision making in routine practice. Currently, we plan to evaluate this prognostic factor in other solid tumors (ovarian carcinoma, lung cancer)51 and also to explore the mechanisms of such lymphopenia.…”
Section: Discussionmentioning
confidence: 99%
“…could modify clinical practice and thereby permit to use lymphopenia for decision making in routine practice. Currently, we plan to evaluate this prognostic factor in other solid tumors (ovarian carcinoma, lung cancer)51 and also to explore the mechanisms of such lymphopenia.…”
Section: Discussionmentioning
confidence: 99%
“…and additionally CTC count as a 4th factor (hereafter called the RMH 2010 prognostic score). In addition, we applied to our series 5 previously reported phase I prognostic scores (Supplementary Table S1): Chicago (8), Oxford (5), Lyon (4), Lille (9,24), and MD Anderson (10). We compared the RMH 2008 and RMH 2010 prognostic scores with the other scores, and evaluated their performance in predicting 90-day mortality using receiver operating characteristic (ROC) curves and comparing their areas under the curves (AUCs) using a nonparametric statistical method based on the Mann-Whitney Ustatistic (25,26).…”
Section: Translational Relevancementioning
confidence: 99%
“…Penel et al [9] analyzed 148 patients who were screened for phase I trial entry from 1997 to 2002 and identified albumin < 38 g/L and lymphocyte count < 700/mm 3 to be independent predictors of 90DM. The same authors validated these predictors in a cohort of 128 patients treated with cytotoxic agents from 1986 to 1993 at a separate center [5]. To date, no risk index has been prospectively validated to predict 90DM.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective reviews by large phase I groups have demonstrated that approximately 25% to 33% of patients do not meet the necessary eligibility criteria at screening [1,2]. In addition, up to 20% of patients die within the first 90 days of PIT entry [3-5]. These early deaths on study are usually attributed to disease progression, as contemporary PIT are safe with a toxic death rate of around 0.5% [3,6-9].…”
Section: Introductionmentioning
confidence: 99%